2017
DOI: 10.3399/bjgp17x688873
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of venous thromboembolism in care homes: a prospective cohort study

Abstract: BackgroundCare home residents have venous thromboembolism (VTE) risk profiles similar to medical inpatients; however, the epidemiology of VTE in care homes is unclear.AimTo determine the incidence of VTE in care homes.Design and settingObservational cohort study of 45 care homes in Birmingham and Oxford, UK.MethodA consecutive sample of care home residents was enrolled and followed up for 12 months. Data were collected via case note reviews of care home and GP records; mortality information was supplemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
12
1
5
Order By: Relevance
“…In both studies, a majority of individuals were long-time NH residents at study start. Thus, our finding of an inverse association between incident VTE and time since admission may contribute to lower estimates of NHVTE/100,000 NH-PY (1,390–1,580[30] and 830[28], respectively) compared to our estimate of 3,653.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…In both studies, a majority of individuals were long-time NH residents at study start. Thus, our finding of an inverse association between incident VTE and time since admission may contribute to lower estimates of NHVTE/100,000 NH-PY (1,390–1,580[30] and 830[28], respectively) compared to our estimate of 3,653.…”
Section: Discussioncontrasting
confidence: 87%
“…Comparison with other findings is hampered by multiple between-study differences (e.g., exclusion rules, person-years-at-risk, and calendar years of study). Of very few investigations of NHVTE incidence and associated mortality,[2831] most were limited by reliance on diagnosis/procedure codes obtained from NH administrative data and/or Medicare claims. As part of a previous study,[32] we compared characteristics of first VTE events among NH residents identified using International Classification of Diseases ( ICD-9-CM ) diagnosis codes[33] from NH administrative data[34] with those for REP-identified VTE events using detailed medical-record review among Olmsted County residents of the same nursing homes during the same time period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the third leading cause of death associated with cardiovascular diseases after ischemic heart disease and stroke [4]. Hospitalization is among the major risk factors of VTE [5]. This study was concerned with the risk factors and integrated intervention measures for DVT among the inpatients.…”
Section: Discussionmentioning
confidence: 99%